PENGARUH INDIKATOR PENILAIAN KESEHATAN BANK DENGAN METODE RGEC DAN ASSET QUALITY TERHADAP HARGA SAHAM PERBANKAN YANG LISTING DI BEI PERIODE 2012-2016 - Suci Atiningsih; Ana Nur Royham (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
The aim of this research is to determine about the impact of banks health rating with RGEC method and asset quality on the stock price. This research is quantitative with use secondary data. Dependent variable in this research is stock price, while independent variable in this research is risk profile factor is proxied by non performing loan (NPL) ratio, the result of self –assessment good corporate governances (GCG) factor, earnings factor are proxied by return on asset (ROA) ratio, return on equity (ROE) ratio, capital factor is proxied by capital adequacy ratio (CAR), and asset quality factor is proxied by non performing asset (NPA) ratio. The sample in this research is 15 banks of company are listing in BEI with observation 3 years. For sample is using purposive sampling method. Data analyzed with descriptive statistical test, multiple linier regression test, classical assumption test, goodness of fit, and data processed by SPSS. The result in this research indicated that NPL and CAR are haven’t effect to stock price, GCG, ROA,and ROE are have positives effect to stock price, while NPA is have negative effect to stock price.